Hyers-Ulam-Rassias stability of functional equations in nonlinear analysis - Jung, Soon-Mo (Springer optimization and its applications, 2011)
This textbook at the advanced undergraduate/graduate level will complement the books of D.H. Hyers, G. Isac, and Th.M. Rassias (© Birkhauser 1998) and of S. Czerwik (2002) by integrating and presenting the primary developments applying to almost all the classical results of  the Hyers-Ulam-Rassias stability. The self-contained text is presented in an easy to understand fashion and all the necessary materials and information are included in order to appeal to a diverse audience with interests in difference and functional equations and functional analysis. Highlights of the text include discussions of the method of invariant means and the fixed point method,  the stability problems for the exponential functional equations, Hyers-Ulam stability, Hyers-Ulam-Rassias stability, Pexider equation, and superstability of the exponential function.